SISTEM OTOMATISASI DISTRIBUSI AIR MENGGUNAKAN SPEED DRIVE INVERTER - Pasila, Felix; Limboto, Limboto; Mardany, Fandy (Jurnal Teknik Elektro, 2001)
Our daily need about water is absolutely essential. Therefore we need some equipments which can support to supply the water accordance with our needed. For example%2C to supply the water in hotel%2C the greater the amount of using the water then we need performance of water pump more and more to move the water from low surface to the higher. However%2C often using of pump is not comparable with our needed and the pump is often operated continually so there are some electrical power and some water that neglected. In this paper%2C the using of water pump will be controlled by speed drive inverter. Motor pump can be arranged so output rate flow of the pump that become accordance with load of using of the water. The controlling of motor is done by inverter by change the frequency%2C but automation is controlled by PLC by using limit switch as sensor of elevated at reservoir and as varian frequency input on inverter%2C also we use pressure switch as automation on-off pump with pressure method. On testing of performance of the equipments%2C obviously it shows total of efficiency of system is not very big. For arranging 35-50 Hz%2C total efficiency reaches only 14 %25. Abstract in Bahasa Indonesia : Kebutuhan harian akan air adalah mutlak. Karena itu dibutuhkan peralatan bantu yang mampu menyuplai air sesuai dengan kapasitas kebutuhan. Untuk aplikasi suplai air di Hotel%2C semakin banyak pemakaian air membutuhkan semakin besar kinerja Pompa air untuk memindahkan air dari permukaan rendah ke permukaan lebih tinggi. Namun seringkali pemakaian pompa tidak sebanding dengan kapasitas kebutuhan dan pompa seringkali dioperasikan terus menerus sehingga ada daya listrik dan air terbuang percuma. Pada paper ini%2C pemakaian pompa air akan dikontrol oleh Speed Drive Inverter motor penggerak pompa bisa diatur sehingga debit output pompa sesuai dengan beban pemakaian air. Pengaturan putaran motor dilakukan oleh Inverter dengan merubah frekuensi.%2C sedangkan otomatisasinya dikendalikan oleh PLC dengan Limit Switch sebagai sensor ketinggian di tandon dan sebagai input variasi frekuensi pada inverter%2C juga digunakan Pressure Switch sebagai On-off otomatis pompa dengan prinsip tekanan. Pada pengujian performansi alat%2C ternyata menunjukkan bahwa efisiensi total sistem tidak terlalu besar. Untuk pengaturan frekuensi 35-50 Hz%2C efisiensi totalnya hanya mencapai 14 %25. Pump+Automation%2C+limit+switch%2C+PLC%2C+Speed+Drive+Inverter